LEGAL IMPLICATIONS TO FIDUSIAN OBJECT WARRANTIES THAT HAS NOT BEEN REMOVED (ROYA) AND RE-REGISTERED ON THE FIDUSIAN ONLINE APPLICATION - Hardianti Hardianti; Akhmad Khisni (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
In Law Number 42 of 1999 concerning Fiduciary Security, it is stipulated that fiduciary security must be registered. Based on the Circular of the Directorate General of General Legal Administration No. AHU-06.OT.03.01 Year 2013 concerning the Enforcement of the Fiduciary Security Registration Administration System electronically (online), the registration process is no longer done manually. In Article 25 of Law Number 42 Year 1999 it is stipulated that after the debt from the fiduciary has been paid, there must be a report regarding the termination of the fiduciary guarantee. Lack of public awareness, especially fiduciary recipients, their proxies or representatives to apply for removal of fiduciary security objects that have ended at the Fiduciary Registration Office, henceforth, it is written off in the ONLINE Fiduciary Register Book which is mandated by the Fiduciary Security Law which may affect the administration of registration of the object of guarantee. This is important to avoid being re-imposed on objects of collateral that are still registered and also to protect the interests of the new creditors. The problems that arise areLegal Implications for Fiduciary Object Collateral That Has Not Been Deleted (Roya) And Re-registered In The ONLINE Fiduciary Application.From the results of the research that has been carried out, it is found that the legal certainty of fiduciary guarantees that registration is not deleted (roya) is in Article 25 of Law Number 42 of 1999 where the fiduciary recipient notifies the abolition of fiduciary guarantees to the Fiduciary Registration Office, this is added with Article 17 Government Regulation Number 21 of 2015 concerning Fiduciary Security Registration Procedures and Fees for Fiduciary Security Deed with a ban on re-fiduciary action. However, the lack of awareness of fiduciary recipients, proxies, or representatives and the absence of strict sanctions regarding the obligation to write off registration (roya) are obstacles in guaranteeing legal certainty for fiduciary security.Deletion of registration (roya) becomes legal protection for parties both juridically and administratively and provides certainty for the object that is guaranteed.